Gradual increases in sugar concentration enhance total perceived sweetness in individuals prone to sweetness habituation - Nitto, Ryota; Ban, Yuki; Fukui, Rui; Warisawa, Shin'ichi (Frontiers in Psychology, 2025)
IntroductionExcessive sugar consumption has become a major health concern, contributing to obesity and diabetes. To address this issue without increasing sugar intake, various strategies to enhance sweetness have been explored. However, conventional methods, which rely on repetitive stimuli or patterns, fail to counteract the decline in perceived sweetness caused by habituation during continuous consumption.MethodsWe hypothesized that gradually increasing sugar concentration during consumption could mitigate habituation and enhance overall sweetness perception. To test this hypothesis, we developed a system capable of delivering sucrose solutions with gradually changing concentrations. In the experiment, participants consumed a 15-second continuous flow of sucrose solution with an average concentration of 4.7%. The sugar concentration either increased from 3.8% to 5.6%, decreased from 5.6% to 3.8%, or remained constant. Participants were instructed to swallow at 3-second intervals for a total of five times, rating sweetness after each swallow. The total perceived sweetness, measured as the Area Under the Curve (AUC), was compared across conditions.ResultsIn groups showing habituation under constant concentration, the increasing concentration condition improved total perceived sweetness.DiscussionThese findings suggest that increasing sugar concentration patterns can alleviate habituation and enhance sweetness perception, particularly in individuals prone to sweetness habituation.